2021
DOI: 10.1371/journal.ppat.1009276
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical transmission of prions by blood transfusion is influenced by donor genotype and route of infection

Abstract: Variant Creutzfeldt-Jakob disease (vCJD) is a human prion disease resulting from zoonotic transmission of bovine spongiform encephalopathy (BSE). Documented cases of vCJD transmission by blood transfusion necessitate on-going risk reduction measures to protect blood supplies, such as leucodepletion (removal of white blood cells, WBCs). This study set out to determine the risks of prion transmission by transfusion of labile blood components (red blood cells, platelets, plasma) commonly used in human medicine, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 43 publications
0
46
1
Order By: Relevance
“…PMCA analysis of serial tenfold dilutions of samples that tested positive showed that the limits of detection were reached at dilutions of 10 –1 –10 –4 (Table 2 ). In comparison, with tissues from pathology positive sheep, the limits of detection were reached at dilutions of 10 –9 –10 –10 for brain 15 and 10 –6 –10 –9 for PSLN (Fig. 1 ; Table S1 ).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…PMCA analysis of serial tenfold dilutions of samples that tested positive showed that the limits of detection were reached at dilutions of 10 –1 –10 –4 (Table 2 ). In comparison, with tissues from pathology positive sheep, the limits of detection were reached at dilutions of 10 –9 –10 –10 for brain 15 and 10 –6 –10 –9 for PSLN (Fig. 1 ; Table S1 ).…”
Section: Resultsmentioning
confidence: 98%
“…Previous data suggested that the PRNP codon 141 polymorphism (L141F), which is associated with statistically significant differences in incubation period in BSE-infected sheep 17 , might also influence the extent of PrP Sc deposition in lymphoid tissues 15 . On average, 141LL sheep had the shortest incubation periods and the most widespread deposition of PrP Sc in lymphoid tissue, whilst 141LF sheep had the longest survival periods and more restricted distribution of PrP Sc in lymphoid tissues.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations